Pengaruh Diskon dan Kualitas Produk Terhadap Perilaku Pembelian Impulsif Konsumen Shopee di RT 010 RW 010 Cempaka Baru Jakarta Pusat - Salsabila, Farah Zahra; Sabariah, Etika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The development of e-commerce such as Shopee has changed people's shopping behavior, including increasing impulse buying tendencies. External factors such as discounts and product quality play an important role in triggering spontaneous purchasing decisions. This study aims to determine the effect of discounts and product quality on impulse buying behavior of Shopee consumers in RT 010 RW 010 Kelurahan Cempaka Baru, Central Jakarta This study uses a quantitative approach by distributing questionnaires to 31 heads of households of Shopee users as respondents using the purposive sampling technique. The t test results show that discounts (t count= 3.555; sig. = 0.001) and product quality (t count = 4.411; sig. = 0.000) have a positive and significant effect on impulse purchases partially. The F test results show that discounts and product quality simultaneously have a significant effect (F count = 76.941; sig. = 0.000). The coefficient of determination (R²) of 0.846 indicates that the two variables are able to explain 84.6% of the variation in impulse purchases. This finding confirms that discount strategies and product quality improvements play an important role in driving impulse purchases on the Shopee e-commerce platform.